MISTERY BOX SEBAGAI MEDIA PEMBELAJARAN UNTUK MENINGKATKAN KEMAMPUAN KOGNITIF KOMPETENSI SIKLUS AKUNTANSI PERUSAHAAN DAGANG - DIAH ARUMSASI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2022)
Conventional learning tends to be teacher-centered, making learning monotonous and boring, students are not active and lazy so that student understanding becomes low. The use of the right media can be a stimulus for students to be more enthusiastic in participating in the teaching and learning process. This requires creative ideas from the teacher as a designer and implementer of learning scenarios in the classroom. The purpose of this study is to find out whether the Problem Base Learning Model can improve students' understanding and mastery of the concept of the Trading Company Accounting Cycle. This Best Practice also uses recycled materials in the form of cardboard which is formed as a medium called